Carbon isotope discrimination in forest and pasture ecosystems of the Amazon Basin, Brazil - Ometto, Jean Pierre Henry Balbaud; Flanagan, Lawrence B.; Martinelli, Luiz Antônio; Moreira, Marcelo Z.; Higuchi, Niro; Ehleringer, James Russell (Global Biogeochemical Cycles, 2002)
Our objective was to measure the stable carbon isotope composition of leaf tissue and CO2 released by respiration (δr), and to use this information as an estimate of changes in ecosystem isotopic discrimination that occur in response to seasonal and interannual changes in environmental conditions, and land-use change (forest-pasture conversion). We made measurements in primary forest and pastures in the Amazon Basin of Brazil. At the Santarém forest site, δr values showed a seasonal cycle varying from less than -29‰ to approximately -26‰. The observed seasonal change in δr was correlated with variation in the observed monthly precipitation. In contrast, there was no significant seasonal variation in δr at the Manaus forest site (average δr approximately -28‰), consistent with a narrower range of variation in monthly precipitation than occured in Santarém. Despite substantial (9‰) vertical variation in leaf δ13C, the average δr values observed for all forest sites were similar to the δ13C values of the most exposed sun foliage of the dominant tree species. This suggested that the major portion of recently respired carbon dioxide in these forests was metabolized carbohydrate fixed by the sun leaves at the top of the forest canopy. There was no significant seasonal variation observed in the δ13C values of leaf organic matter for the forest sites. We sampled in pastures dominated by the C4 grass, Brachiaria spp., which is planted after forest vegetation has been cleared. The carbon isotope ratio of respired CO2 in pastures was enriched in 13C by approximately 10‰ compared to forest ecosystems. A significant temporal change occured in δr after the Manaus pasture was burned. Burning removed much of the encroaching C3 shrub vegetation and so allowed an increased dominance of the C4 pasture grass, which resulted in higher δr values.
Keywords: Biogeochemical Cycle; Carbon Isotope; Environmental Change; Land-use Change; Leaf; Respiration; Terrestrial Ecosystem; Tropical Environment; Amazonia; Brachiaria